I can look for it! Modulation of a concurrent Visual Working Memory task in Visual Search in development - Quirós-Godoy, María; Gil-Gómez de Liaño, Beatriz; Perez-Hernandez, Elena (Frontiers in Psychology, 2022)
Daily classroom activities that require children to perform visual search (VS) tasks are common across all educational levels: from searching a missing piece of a puzzle in Kindergarten to resolving equations in College. However, VS tasks are often not performed in isolation, but rather students are maintaining information related to an ongoing task that loads Working Memory (WM). Unfortunately, it is still unclear how these processes interact and evolve in development. The present work aims to study how a concurrent Visual WM (VWM) load can modulate VS performance based on the Developmental Model of Endogenous Mental Attention (Pascual-Leone & Johnson, 1999, 2005, 2021). A sample of Kindergarten, Elementary (2nd & 4th grades), Middle School (6th grade), and College students looked for real-world photorealistic targets while maintaining similar objects in VWM within a dual-task paradigm. VWM load was manipulated using high and low memory load conditions. Additionally, looking for potential modulations related to individual differences, we studied the relationship between IQ, VWM span, and executive functions with VS efficiency. Finally, we also registered reported measures of potential strategies employed during the VS task. Results from a large sample of 147 participants between 5 and 25 years old revealed that even the youngest children could efficiently perform a VS task with a concurrent VWM load, replicating previous results found in adulthood. However, we found a slight increase in false alarms and commission errors when memory was highly loaded for all participants, regardless of age. As expected, we found positive correlations between VS efficiency and IQ and VWM span measures. Interestingly, the proportion of participants who used tracking organization strategies increased with age in all cases. However, although cognitive strategies to remember the target became more complex as age increased, it was only significant under low VWM load conditions. The results seem relevant to understanding the development of VS based on the Model of Endogenous Mental Attention and the design of training programs to improve attention. The implications in educational contexts are discussed, especially relevant for students with learning disabilities or attention problems.